Wagner's «Der Fliegende Hollander»: a colourful tale of dreams and wanderings - Roschenko, Olena (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study. The study of R. Wagner's opera «Der Fliegende Hollander» from the standpoint of reflecting in it the genre features of the art fairy tale requires the use of those philosophical and aesthetic concepts in the context of which the artistic phenomena that form the research material in this scientific work matured. Achieving the aim of the study required relying on the doctrine of ‘transcendental philosophers’ about the «work of art of the future» as an example of a «new myth» reproduced in the form of an ‘encyclopaedia-chaos in the fragmentary form of arabesque’ [Рощенко, 2006], and on the theory of the art fairy tale set out in the Fragments by Novalis and F. Schlegel. The paradigmatic role was played by the genre features of Kunstmärchen in Wagner's opera Der Fliegende Hollander, one of the prototypes of which was W. Hauf's The Story of the Ghost Ship. Its influence on Wagner's musical drama is not limited to plot parallels, but is also observed at the level of a type of dramaturgy (fragmentary dream drama), the role of the frame principle in the «caravan» unification of stories about the fate of the cursed Captain, the influence of «Gothic novel». The discovery of the Kunstmärchen system of features has led to the expediency of genre definition of Wagner's opera as a colourful tale of dreams and wanderings. The rampage of «dark fantasy», which is overcome by the hero's final accession to the saving peace, allowed us to identify in Der Fliegende Hollander the signs of synthesis ofof such genre types as «horror opera» and «salvation opera». The interaction of these genre types allowed us to define «Der Fliegende Hollander» as an «opera of horrors and salvation». The main objective of the study is to identify the genre features of the artistic fairy tale in Richard Wagner's opera Der Fliegende Hollander based on the analysis of the philosophical and artistic context of German Romanticism. The methodology includes the principle of historicism; comparative analysis; analysis of intonation dramaturgy; encyclopaedic analysis (O. Roschenko, 2006), designed to establish the range of literary influences observed in the drama of Wagner's Der Fliegende Hollander as a colourful tale of dreams and wanderings. Results and conclusions. The definition of Kunstmärchen features in the dramaturgy of Wagner's «Der Fliegende Hollander», based on the key positions of the works of «transcendental philosophers» regarding the interpretation of the work of «art of the future» as a «new myth», has made it possible to define the genre of musical drama as a tale of dreams and wanderings with the features of a «Gothic novel», as a «opera of horror and salvation». It is revealed that the influence of W. Hauf's Kunstmärchen is not limited to plot parallels, but is observed at the level of the logic of the development of the action according to the type of «motley sheets», which ultimately form a special type of opera drama, defined as dream drama